2005
DOI: 10.1379/csc-250
|View full text |Cite
|
Sign up to set email alerts
|

HSF2 Binds to the Hsp90, Hsp27, and c-Fos Promoters Constitutively and Modulates their Expression

Abstract: Although the vast majority of genomic DNA is tightly compacted during mitosis, the promoter regions of a number of genes remain in a less compacted state throughout this stage of the cell cycle. The decreased compaction of these promoter regions, which is referred to as gene bookmarking, is thought to be important for the ability of cells to express these genes during the following interphase. Previously, we reported a role for the DNA-binding protein heat shock factor (HSF2) in bookmarking the stress-inducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The results are representative of the banding pattern observed from western blot analysis of two independent mouse sperm protein isolations, and indicate that RNA Polymerase II is present in mature spermatozoa. In both the sperm lane (left image) and C2C12 lane (right image) we observed one predominant band migrating at approximately 220kDa that is consistent with the size of RNA Polymerase II detected in previous studies (Luthi-Carter et al 2002; Wilkerson et al 2007). …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results are representative of the banding pattern observed from western blot analysis of two independent mouse sperm protein isolations, and indicate that RNA Polymerase II is present in mature spermatozoa. In both the sperm lane (left image) and C2C12 lane (right image) we observed one predominant band migrating at approximately 220kDa that is consistent with the size of RNA Polymerase II detected in previous studies (Luthi-Carter et al 2002; Wilkerson et al 2007). …”
Section: Resultssupporting
confidence: 90%
“…Previously, we observed in Jurkat cells blocked in mitosis that the binding of RNA Polymerase II to a number of HSE containing promoters was reduced, but not completely eliminated (Wilkerson et al 2007). There was clear and reproducible binding of RNA Polymerase II to the promoters of Hsp90aa1 (Hsp90), fos, and Hspb1 (Hsp27) in mitotic cells.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that the putative HSF binding site may indirectly modulate the CCR5 expression and thus HIV‐1 replication. Activated HSF2 induces the expression of heat shock protein 70 (HSP70; Wilkerson et al ., ), which in turn stimulates the expression of CCR5 in CD4 T cells and dendritic cells. This leads to increased expression of APOBEC3G enzyme that is known to have antiviral activity via deaminating viral cytidine to uridine and thus making the HIV‐1 virion nonfunctional (Whittall et al ., ; Pido‐Lopez et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently our laboratory has shown that HSF2 can bind to the promoters of Hsp27 , Hsp90 , and C-fos in mitotic cells [57]. Other genes, many of which are members of the heat shock superfamily, are also bound by HSF1 and HSF2 [58].…”
Section: Discussionmentioning
confidence: 99%